The Effectiveness of Using Recreational Educational Activities in Developing Listening and Speaking Skills in Loghati Course for Third Graders - Al- Hersh, Mesfer Saud Mubarak (Journal of Educational and Psychological Sciences, 2020)
The study aimed to reveal the effectiveness of using educational activities based on entertainment in development listening and speaking skills in the Arabic language course (Loghati) of the third- grade students. To achieve this، the researcher followed the semi-experimental approach based on creating two groups: experimental group and control group. He also prepared a number of activities that contain entertainment with selecting number of listening and speaking skills that are related to the course goals and content. In addition to that, he designed listening test، speaking situations and note card for speaking skills. The study sample consisted of (28) students divided into two groups: an experimental group of (14) students and a control group of (14) students. The researcher pre-tested the students in listening and speaking. The results showed no statistically significant differences between the two groups. After that، the experimental group studied using entertainment-based activities، while the control group studied in the usual way. At the end of the application the two groups were post-tested in listening and speaking، the study results were as follows: There were statistically significant differences between the average grades of the experimental and control groups in the listening post-test in favor of the experimental group. There were statistically significant differences between the average grades of the experimental and control groups in the speaking post-test in favor of the experimental group. Considering the findings of the study، several recommendations were presented: Add educational activities based on entertainment in the Arabic language course (Loghati); to assist in the development of listening and speaking skills. Ask Arabic teachers’ assessments to focus on teachers’ attention in developing listening and speaking skills and giving them as much importance as other language skills.